Philosophy and Religion in German Idealism - Desmond, William; Onnasch, Ernst-Otto.; Cruysberghs, Paul.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
This volume comprises studies written by prominent scholars working in the field of German Idealism. These scholars come from the English speaking philosophical world and Continental Europe. They treat major aspects of the place of religion in Idealism, Romanticism and other schools of thought and culture. They also discuss the tensions and relations between religion and philosophy in terms of the specific form they take in German Idealism, and in terms of the effect they still have on contemporary culture. The authors consider figures such as Kant, Fichte, Hegel, and Jacobi. The book will prove very informative to researchers and teachers working in the fields of philosophy, philosophy of religion, and classical German philosophy.
Philosophy of Religion After the Death of God -- Kant on Religion in the Role of Moral Schematism -- "Wishful Thinking" Concerning Fichte's Interpretation of the Postulates of Reason in His Versuch Einer Kritik Aller Offenbarung (1792) -- The Unsatisfied Enlightenment Faith and Pure Insight in Hegel's Phenomenology of Spirit -- Religion, Morality and Forgiveness in Hegel's Philosophy -- The Finite Does Not Hinder Hegel's Philosophy of Christian Religion Placed Against the Backdrop of Kant's Theory of the Sublime -- Hegel on Reason, Faith and Knowledge -- Religion and the Poverty of Philosophy.
Keywords: PHILOSOPHY (GENERAL).; PHILOSOPHY, MODERN; PHILOSOPHY; PHILOSOPHY; PHILOSOPHY OF RELIGION; MODERN PHILOSOPHY